LITERASI KEUANGAN SERTA PENGGUNAAN PRODUK DAN JASA LEMBAGA KEUANGAN - Sri Lestari (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2015)
This study entitled: "Financial Literacy and Utility Products and Services Financial Institutions". The purpose of this research are: 1) Knowing and analyzing the financial literacy index of financial products and services to the students of the faculty of Economics and Business jenderal Soedirman University 2) Knowing and analyzing the utility index products and financial services to the students of Economics and Business Faculty; ; 3) Knowing and analyzing the causes and the high barriers to low index Financial Literacy and utility products and financial services among the students of the Faculty of Economics and Business Faculty; 4) Determine and analyze whether the effort made by Fiancial Service Autority, Financial Institutions and the Program to improve the financial literacy of students; 5) Provide input to the Financial Services Authority and the Program in preparing the financial literacy materials needed to improve students understanding of financial products and services. This research is a qualitative descriptive method analysis using informants population and students of the Faculty of Economics and Business UNSOED, the Financial Services Authority officials, managers of Studies, and Financial Institutions Officer. The results showed that financial literacy index of financial institutions that exist in Indonesia at the FEB students Unsoed still low at only $ 4.76 for students who are well literate and amounted to 95.24% in banking products and services. Causes and high barriers to low index of Literacy Financial and utility products and financial services among the students of the Faculty of Economics and Business UNSOED is: do not get the financial education of the family as a child (80%), not taught in formal education as a child (77%), not to get the material and a deep understanding of the subjects were obtained during the study (70%), and the limited funds received from parents and therefore can not be used to invest in products and services of financial institutions (93%). Therefore, the financial services authority need to be more intensive in propagating financial literacy program for students with conduct socialization activities continuously. While the Program need to improve financial learning with learning innovation, identifying subjects that are relevant to the Financial Literacy material, determine appropriate teaching methods and reviewing the curriculum back.